COMPARISON OF NASAL CARRIAGE OF MRSA AND ITS ANTIBIOTIC SUSCEPTIBILITY WITH SPECIAL REFERENCE TO MUPIROCIN AMONG STUDENTS OF HEALTH-CARE SETTINGS AND OTHER STUDENTS - M, Bharathi; T, SIRISHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: One of the potential risk factors for nosocomial staphylococcal and Methicillin-resistant Staphylococcus aureus (MRSA) infections is colonization of the anterior nares of HCWs, and from there they may spread to the patients, which may cause a burden on the health-care system. In this context, we made an attempt to compare the Staphylococcal and MRSA nasal carriage and their susceptibility to Mupirocin in students who are exposed to the health-care system and those who are not. Methods: Nasal swabs were collected from 100 paramedical students as the study group and 100 non-medical students as the control group, all in the age group between 18 and 21 years. 5% sheep blood agar and mannitol salt agar were used to isolate S. aureus, and antibiotic sensitivity was done by Kirby Bauer Disc Diffusion Technique. Cefoxitin disc (30 μg) and Vancomycin screen agar were used to detect MRSA and Vancomycin resistance, respectively. A 5 μg disc of Mupirocin was used to test the susceptibility of Mupirocin. Results: Nasal carriage rate of S. aureus and MRSA was 23% and 8% in Paramedical students and 17% and 4% in Nonmedical students respectively. 83% of isolates from paraclinical students and 95% of isolates from non-medical students were susceptible to linezolid. Out of 12 MRSA strains from both groups only one strain showed resistance to Mupirocin. Conclusions: Nasal carriage of S. aureus and MRSA and antibiotic resistance of isolated strains were more common in paramedical students and also in female students. Vancomycin resistance was not observed in MRSA strains from male students. Mupirocin resistance, even in a single case, needs to be addressed.